First attempt success with continued versus paused chest compressions during cardiac arrest in the emergency department. (May 2023) - Robinson, Aaron E.; Driver, Brian E.; Prekker, Matthew E.; Reardon, Robert F.; Horton, Gabriella; Stang, Jamie L.; Collins, Jacob D.; Carlson, Jestin N.
Abstract: Aim: Tracheal intubation is associated with interruption in cardiopulmonary resuscitation (CPR). Current knowledge of tracheal intubation during active CPR focuses on the out-of-hospital environment. We aim to describe characteristics of tracheal intubation during active CPR in the emergency department (ED) and determine whether first attempt success was associated with CPR being continued vs paused. Measurements: We reviewed overhead video from adult ED patients receiving chest compressions at the start of the orotracheal intubation attempt. We recorded procedural detail including method of CPR, whether CPR was continued vs paused, and first attempt intubation success (primary outcome). We performed logistic regression to determine whether continuing CPR was associated with first attempt success. Results: We reviewed 169 instances of tracheal intubation, including 143 patients with continued CPR and 26 patients with paused CPR. Those with paused CPR were more likely to be receiving manual rather than mechanical chest compressions. Video laryngoscopy and bougie use were common. First attempt success was higher in the continued CPR group (87%, 95% CI 81% to 92%) than the interrupted CPR group (65%, 95% CI 44% to 83%, difference 22% [95% CI 3% to 41%]). The multivariable model demonstrated an adjusted odds ratio of 0.67 (95% CI 0.17 to 2.60) for first attempt intubation success when CPR was interrupted vs continued. Conclusions: It was common to continue CPR during tracheal intubation, with success comparable to that achieved in patients without cardiac arrest. It is reasonable to attempt tracheal intubation without interrupting CPR, pausing only if necessary.